How can Experian derive business value through joining up its capabilities to create innovative product proposals? - Tasmaya, Pramadita (2008)
Experian is a global company; the main business of Experian is in providing information, analytical and marketing services to organisations and consumers to help manage the risk and reward of commercial and financial decisions. The company combines its unique information tools and deep understanding of individuals, markets and economies; Experian also supports their clients in providing them business insights about the business strategy, acquire customers profitability and maximise the value of their existing customers. In the UK, Experian managed more than 600 clients in different type of industries, including financial services, retail, home shopping, telecommunications, utilities, media, insurance, automotive, leisure, charity and property. Moreover, Experian also helps public sector organisations in making better decisions around policy formulation and efficient service delivery. The project is intended to expand the business of Experian by entering a new market with an innovative product and service. The main source of data is anticipated to be the employees at the firm. Face to face interviews are likely to be the most productive method of obtaining information from people. The interview was conducted with more than 26 people in the company from different departments, this was initiated to gain as many information as I could get for the project. In addition to the interview, I've also done a lot of research from the company intranet, websites, and journals to get more insight about the business and search for some opportunities that would be valuable to the company. The main objective of the project is to link the internal capabilities of Experian with the customer needs; the linkage would be the outcome that will propose several new potential product and services.